2018
DOI: 10.1515/sjecr-2017-0024
|View full text |Cite
|
Sign up to set email alerts
|

Cone-Beam Computed Tomography Study of the Root Canal Morphology of Mandibular Anterior Teeth in Serbian Population

Abstract: Th e aim of this study is to describe the morphological characteristics, the number of roots and number of root canals of mandibular central incisors, lateral incisors and canines, and the relationship of these characteristics with the sex and the jaw side where the tooth is located, in the Serbian population using cone-beam computed tomography (CBCT).CBCT images of a total of 902 mandible front teeth, including 296 central incisors, 294 lateral incisors and 312 canines were analyzed in the database. For asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 19 publications
(73 reference statements)
0
6
0
2
Order By: Relevance
“…The aim of this study was to evaluate the number of roots and root canal morphology, including canal length, of maxillary and mandibular first and second molars and variations between sexes and side of the jaw. This study is part of a major research of the root morphology, which we conducted at the Faculty of Medical Sciences, University of Kragujevac, Serbia 13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this study was to evaluate the number of roots and root canal morphology, including canal length, of maxillary and mandibular first and second molars and variations between sexes and side of the jaw. This study is part of a major research of the root morphology, which we conducted at the Faculty of Medical Sciences, University of Kragujevac, Serbia 13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…The study of Trope et al demonstrated that premolar teeth with multiple root canals are more frequently observed in black people [16]. Gender diversity in the number of roots and root canals has also been reported [17]. A study of Ok et al showed a higher incidence of single-rooted mandibular premolars in females, while two-rooted and tree-rooted mandibular premolars are more common in males [10].…”
Section: Introductionmentioning
confidence: 99%
“…In a study done in Iranian Population it was found that 12.08 % out of 149 teeth have two [14] roots . While another study done in Serbian [15] population found 5.8% had two roots Han et [16] al. found 1.3 % using CBCT method .…”
Section: Resultsmentioning
confidence: 91%